Calcitonin gene-related peptide monoclonal antibodies and medication-overuse headache: stopping excessive pain medication is still necessary - Pedro Augusto Sampaio Rocha-Filho (Arquivos de Neuro-Psiquiatria, 2025)
Medication-overuse headache affects 1 to 2% of the global population and is often associated with chronic migraine. This condition significantly impacts the lives of patients, as well as their families, and it poses a major economic burden due to lost productivity and medical costs. The present narrative review is part of a controversy session. We argue that reversing the behavior of overusing symptomatic pain medications is important for the treatment of this type of headache. To support this argument, the article reviews and critically analyzes the relevant literature on the subject.